Pengaruh PSBB Volume Perdagangan terhadap Stock Return pada Perusahaan Layanan Perdagangan dan Investasi Sub Sektor Pariwisata Restoran dan Hotel - Maria Marsilinda Paku; Risal Rinofah; Ratih Kusumawardhani (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study aims to analyze the effect of Large-Scale Social Restrictions (PSBB) and trading volume on stock returns of trade and investment service companies in the tourism, restaurant, and hotel sub-sectors. These sub-sectors were selected due to their significant exposure to the impacts of the COVID-19 pandemic, particularly from restrictions on public mobility and face-to-face interactions. This research uses a quantitative method with an associative approach. The data used are secondary data obtained from the Indonesia Stock Exchange (IDX) reports and official government publications related to the PSBB policy during the pandemic. The sample consists of companies in the tourism, restaurant, and hotel sub-sectors listed on the IDX during the 2020–2021 period. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results show that the PSBB variable has a significant negative effect on stock returns, as social and economic restrictions led to decreased corporate revenues. On the other hand, trading volume has a significant positive effect on stock returns, indicating that increased trading activity reflects higher investor interest, which contributes to stock price increases. This study is expected to provide both theoretical and practical insights for companies, investors, and policymakers in understanding capital market dynamics during crises and in formulating appropriate risk mitigation strategies.